Turn-of-the-month (TOM) effect and rest-of-the month (ROM) effect in real estate investment trust (REITs): Singapore / Norhayati A. Salam - A. Salam, Norhayati (2007)
This project paper study on the turn-of-the-month (TOM) effect in Estate Investment Trusts (Reits) in Singapore. The study is using five Reds companies that listed in main board Singapore Stock Exchange from 2002 until 2007. The main objective of this study is to examine whether the seasonality affect can be detected in tea' estate investment trust company in small country like Singapore. The sub Objective is to examine whether the TOM effect exist in real estate investment trust. The other Sub Objective is to examine whether the ROM effect exist in red estate investment trust. The test is using parametric and nonparametric test, The parametric test used by independent sample test and non. parametric test is used by Wilcoxon Signed Ranks (WSR) test. By using the independent sample test in order to test the differences between TOM return and ROM return, shows that there is not significantly difference Bur by looking the mean difference show that the ROM return is grater than the TOM return. By using the WSR to compare between the TOM return and the ROM return shows that two out of five companies have significantly difference the other three companies are hot significantly difference. The result shows that TOM effect can be detected by using non-parametric test not parametric test. Even Singapore is a small country there is also have seasonality effect.